Fabrication of 2-Inch Free-Standing GaN Substrate on Sapphire With a Combined Buffer Layer by HVPE - Liu, Nanliu; Jiang, Yongjing; Xiao, Jian; Liang, Zhiwen; Wang, Qi; Zhang, Guoyi (Frontiers in Chemistry, 2021)
Free-standing GaN substrates are urgently needed to fabricate high-power GaN-based devices. In this study, 2-inch free-standing GaN substrates with a thickness of approximately 250 μm were successfully fabricated on double-polished sapphire substrates by taking advantage of a combined buffer layer using a growth method of hydride vapor phase epitaxy (HVPE) and the laser lift-off technique. Such combined buffer layer intentionally introduced a thin AlN layer, using a mix of physical and chemical vapor deposition at a relatively low temperature, a 3-dimensional GaN interlayer grown under excess ambient H2, and a coalescent GaN layer. It was found that the cracks in the epitaxial GaN layer could be effectively suppressed due to the large size and orderly orientation of the AlN nucleus caused by pre-annealing LT-AlN. With the addition of a 3D GaN interlayer, the crystal quality of the GaN epitaxial films was further improved. The 250-µm thick GaN film showed an improved crystalline quality, and the full width at half-maximums for GaN (002) and GaN (102) respectively dropped from 245 and 412 arcsec to 123 and 151 arcsec, relative to those without the 3D GaN interlayer. The underlying mechanisms for the improvement of crystal quality were assessed. This method may provide a practical route for fabricating free-standing GaN substrates at low cost with HVPE.